The Role of Job Satisfaction in Mediating the Influence of Work Environment On Employee Performance At Freestyle Konveksi - Ni Putu Meisya Prima Sari; Ni Wayan Mujiati; I Gusti Made Suwandana (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Employee performance is influenced by various factors, one of which is the work environment. A less conducive work environment, such as minimal facilities, lack of support from superiors, and inharmonious relationships between employees, can reduce productivity and work performance. The mediating variable in this study is job satisfaction which is expected to further strengthen the work environment on employee performance, with increasing work environment conditions it will improve employee performance. This study aims to determine the role of Job Satisfaction in Mediating the influence of the Work Environment on Employee Performance at Freestyle Konveksi. Based on the results of the pre-survey conducted, there were indications of problems related to Employee performance at the research location. The sample in this study was 32 Employees determined by the saturated sampling method. Data collection was carried out by interviews and distributing questionnaires. The data analysis techniques used in this study were path analysis with SPSS, the Sobel test, and the VAF test. The results of this study indicate that the work environment has a positive and significant effect on employee performance, the work environment has a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on employee performance, and job satisfaction is able to mediate the effect of the work environment on employee performance. The implications of this study theoretically support the findings of previous studies through the perspective of the Two Factor Theory. The practical implications of this study provide policy references for company leaders and employees to improve performance through the work environment and job satisfaction.